2012
DOI: 10.1042/cbi20110432
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acid‐sensing ion channels by amiloride protects rat articular chondrocytes from acid‐induced apoptosis via a mitochondrial‐mediated pathway

Abstract: A significant decrease in tissue pH or acidosis is a common feature of numerous diseases, including RA (rheumatoid arthritis). Cartilage homoeostasis is profoundly affected by local acidosis in the joints. The diuretic, amiloride, is neuroprotective in models of cerebral ischaemia, a property attributable to the inhibition of ASICs (acid-sensing ion channels) by the drug. However, little is known about the effect of amiloride on apoptosis induced by extracellular acid in articular chondrocytes. We have found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…Similarly, the ASIC1a-specific blocker PcTX venom attenuated acid-induced articular chondrocyte damage [25]. Furthermore, blocking ASICs markedly decreased calpain and calcineurin expression levels as well as caspase-3/9 activity, and led to recovery of mitochondrial membrane potential via regulation of B-cell lymphoma-2 family gene expression in acid-induced chondrocytes [9,73]. A more recent study reported that interleukin-6 promotes acid-induced articular chondrocyte apoptosis to a significant extent by activating the JAK2/STAT3 and MAPK/NF-κB signaling pathways, resulting in upregulation of ASIC1a expression and function [4].…”
Section: Asics and Arthritismentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, the ASIC1a-specific blocker PcTX venom attenuated acid-induced articular chondrocyte damage [25]. Furthermore, blocking ASICs markedly decreased calpain and calcineurin expression levels as well as caspase-3/9 activity, and led to recovery of mitochondrial membrane potential via regulation of B-cell lymphoma-2 family gene expression in acid-induced chondrocytes [9,73]. A more recent study reported that interleukin-6 promotes acid-induced articular chondrocyte apoptosis to a significant extent by activating the JAK2/STAT3 and MAPK/NF-κB signaling pathways, resulting in upregulation of ASIC1a expression and function [4].…”
Section: Asics and Arthritismentioning
confidence: 96%
“…Ca 2+ influx into cells is commonly mediated through activating channels or receptors, such as voltage-gated Ca 2+ channels, α-amino-3-hydroxyl-5-methyl-4-isoxazole-propionate receptors, transient receptor potential channels, and N-methyl-Daspartate receptors [8]. Interestingly, ASICs have been shown to play crucial roles in modulating cell behavior via regulation of intracellular Ca 2+ accumulation, including apoptosis [4,9], differentiation [10], and autophagy [11]. Multiple lines of evidence suggest that aberrant expression and activation of ASICs contribute to the progression of various degenerative diseases, including multiple sclerosis, Parkinson's disease, Huntington's disease, intervertebral disc degeneration and arthritis.…”
mentioning
confidence: 99%
“…Therefore, prevention of excessive apoptosis of chondrocytes is believed to be beneficial for OA management. Drugs that can ameliorate OA have been reported to show anti-apoptotic effects on chondrocytes, such as sinomenine (Ju et al 2010), ADAM15 (Böhm et al 2010) and amiloride (Rong et al 2011). Many triterpenoid saponin ingredients in traditional Chinese medicine have anti-apoptotic effects, such as astragaloside (Shang et al 2011), Panax notoginseng saponins , Ginsenoside-Rg2 (Zhang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This signal transduction chain is in keeping with a recent publication (48) that reports a key role for L-type voltage-gated channels in osteoarthritis, evoked and aggravated by mechanical trauma. We consider it an appealing possibility that the chondrocytic Ca 2+ signal of cartilage traumatic injury impacts chondrocytes' cytoskeleton, energy homeostasis, apoptotic equilibrium, and inflammatory phenotype (15,(62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%